The Effect Of Lemon Oil Aromatherapy On Nausea And Vomiting In Pregnant Women (Emesis Gravidarum) - Misrawati; Marliah (Jurnal Life Birth, 2023)
Nausea and vomiting in pregnancy (Emesis gravidarum) occurs in 60-80% of primigravidas and 40-60% of multigravidas. One way to overcome nausea and vomiting in pregnancy is by using lemon aromatherapy. The purpose of this study was to determine the effect of lemon oil aromatherapy on nausea and vomiting in pregnant women (Emesis gravidarum) in the working area of the Kassi Kassi Makassar public health center in 2022. This type of research used pre-experiment with the design of the one group pre-post test design. The sampling technique in this study was purposive sampling which was conducted at the public health center Kassi Kassi Makassar on March 23 to September 23, 2022. The population in this study were all pregnant women who experienced nausea and vomiting (Emesis gravidarum). The sample in this study was 20 respondents and the data were collected using observation sheets. The results of this study showed a decrease in the mean frequency of nausea and vomiting where the mean nausea and vomiting at pretest was 3.55 while on post-test was 0.95. Based on the results of the Wilcoxon Signed Rank Test, the value of p = 0,000 was obtained. Since p = 0.000 <from α = 0.05, it can be concluded that the hypothesis is accepted. This means that there is an effect of lemon oil aromatherapy on nausea and vomiting in pregnant women..